Financial LiteracyAnd Leverage With Adoption of Financial Technology As a Moderating Influence on Financial Well-being - Deanissa Setya Ananda; Alfiatul Maulida; Pristin Prima Sari (Escalate : Economics and Business Journal, 2026)
This research is motivated by the gap between high digital financial inclusion and low financial literacy among urban communities, which triggers an increased risk of default due to debt burden (leverage). This study aims to analyze the influence of financial literacy and leverage on the financial well-being of urban communities in Yogyakarta, as well as to examine the moderating role of financial technology adoption. The research method used a quantitative explanatory approach through the distribution of structured questionnaires to 100 respondents who actively use fintech in Yogyakarta, which were then analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The main findings indicate that financial literacy has a positive and significant effect on financial well-being, while leverage has a negative and significant effect. Furthermore, the adoption of financial technology has been shown to strengthen the positive influence of financial literacy on financial well-being, but lacks the moderating capability to reduce the negative impact of leverage. In conclusion, financial well-being is determined by wise cognitive fund management skills, not simply technology adoption. The implication is that urban communities must be disciplined in controlling consumptive digital debt, while regulators such as the Financial Services Authority (OJK) and Bank Indonesia need to tighten regulations on fintech platforms and expand digital literacy education in a targeted manner